1983
DOI: 10.1063/1.864238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotation on the stability of a bounded cylindrical layer of fluid heated from below

Abstract: The onset of steady natural convection in a rotating cylindrical volume of fluid completely bounded by rigid surfaces is examined for moderate Taylor numbers (Ta≤2×106) and aspect ratios (A≤2). The critical Rayleigh number for three dimensional disturbances is found to be lower than that for the radially unbounded problem by up to a factor of six. The thermal boundary condition on the lateral walls is shown to have a greater effect here than in the nonrotating case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 6 publications
4
24
0
Order By: Relevance
“…We find that the first bifurcation is a Hopf bifurcation to a time-periodic state in which the convective structure precesses in the rotating frame. The spatial symmetry of our pattern agrees qualitatively with a recent linear-stability analysis [3]; but in the theoretical work it was assumed that the structure would be stationary in the rotating frame. An interesting aspect of this instability in the finite system, noticed also in previous heat transport experiments [4,5], is that it occurs at a smaller value of A7" than the predicted value for the infinite system.…”
supporting
confidence: 87%
“…We find that the first bifurcation is a Hopf bifurcation to a time-periodic state in which the convective structure precesses in the rotating frame. The spatial symmetry of our pattern agrees qualitatively with a recent linear-stability analysis [3]; but in the theoretical work it was assumed that the structure would be stationary in the rotating frame. An interesting aspect of this instability in the finite system, noticed also in previous heat transport experiments [4,5], is that it occurs at a smaller value of A7" than the predicted value for the infinite system.…”
supporting
confidence: 87%
“…For b ¼ 1, the critical mode is the antisymmetric m ¼ 1 mode. Using linear stability analyses, Buell and Catton [11] found that Ra cr ¼ 471, while Touihri et al [15] found that Ra cr ¼ 462. Using a numerical time integration of the full three-dimensional Navier-Stokes and energy equations, Neumann [16] found that Ra cr ¼ 451.…”
Section: Resultsmentioning
confidence: 98%
“…In this case, the first instability as the temperature difference is increased involves the transition to a steady axisymmetric or nonaxisymmetric flow. If the cylinder is rotated about its vertical centerline, the base-state consists of a rigid body rotation with the cylinder and a linear temperature variation, with the initial transition to an axisymmetric or nonaxisymmetric flow which is steady in a reference frame rotating with the cylinder [11]. For a fixed, finite-length cylinder with a rotating magnetic field, the base-state consists of (1) the azimuthal velocity v h0 ðr; zÞ driven by the RMF, (2) a meridional circulation which consists of radial and axial velocity components and which is driven by the axial variation of the centrifugal force due to v h0 , and (3) a temperature which deviates from a linear variation due to the convective heat transfer associated with the basestate meridional circulation.…”
Section: Introductionmentioning
confidence: 99%
“…18 In both papers, the thresholds for the mode k = 1 and large aspect ratios ͑height over radius͒ in which we are interested are given as critical curves from which it is difficult to extract precise data. But in another paper of Buell and Catton, 19 numerical data can be found that are given in Table III. These data can then be compared with the results of Rubinov et al 11 For A b =2 ͑heated from below͒, the critical Rayleigh number is Ra cr ͑A b =2͒ = 471.25, which agrees very well with Ra cr ͑A =5͒ = 473 ͑value extracted from Rubinov et al 11 ͒ for the case partially heated from the side.…”
Section: Comparison With the Case Heated From Below For Large Aspect mentioning
confidence: 96%